Optimising indexation arrangements under Calvo contracts and their implications for monetary policy - Vo Phuong Mai Le; Patrick Minford (Cardiff University, Cardiff Business School, 2007)
This paper investigates optimal indexation in the New Keynesian model, when the indexation choice includes the possibility of partial indexation and of varying weights on rational and lagged indexation. It Önds that the Calvo contract adjusted for rationally expected indexation under both ináation and price level targeting regimes delivers the highest expected welfare under both restricted and full current information. Rational indexation eliminates the eectiveness of monetary policy on welfare when there is only price-level targeting under the current micro information. If including both wage setting and full current information, monetary policy is eective; and a price-level targeting rule delivers the highest beneÖts because it minimises the size of shocks to prices and thus dispersion. However, even less than full rational indexation ensures that there is very little nominal rigidity in the adapted world of Calvo contracts.
Keywords: E50; E52; 330; optimal indexation; price-level target; inflation target; Calvo contracts; rational expectation; New Keynesian model; Vertragstheorie; Geldpolitik; Inflation Targeting; Indexierung; Wohlfahrtsanalyse; Rationale Erwartung; Neukeynesianische Makroökonomik